Working conditions, health and retirement intentions: a case study of truck drivers - Sousa, I. C.; Ramos, S. (International Journal of Workplace Health Management, 2018)
Purpose. Being a professional truck driver implies prolonged exposure to physical and psychosocial risks, which can affect health and work ability in the short and long term. The purpose of this paper is to examine the role of working conditions in truck drivers’ perceived health and retirement intentions in a Portuguese transportation company. Design/methodology/approach. Using ergonomic work analysis (EWA), this study incorporates document analysis, observation and 16 interviews. Content analysis is applied to interviews’ transcripts. Findings. In line with previous research, drivers acknowledged their activity as physically demanding (e.g. static postures, repetitive movements, heavy lifting) and psychologically demanding (e.g. high time pressure, lack of control, lack of work–family balance). Despite that, drivers report themselves to be in good health, with only some complaints related to back and knee pain. However, hard working conditions associated with ageing can contribute to gradual health deterioration, leading them to desire to retire before the legal retirement age. Practical implications. The company can promote drivers’ health by creating a unit to provide psychosocial support and career orientation, improving the mentoring programme, and investing in training on occupational risk prevention. Originality/value. This study is the first to use EWA to examine the impact of the complex relationship between truck drivers’ work and health in their retirement intentions, adopting a temporal perspective.